Effect of Team-Pair-Solo Strategy on Senior Secondary School Students’ Performance in Mathematics - Sojinu, Sehubo Olawale; Sanni, Rasheed; Akudo, Kennedy O.; Chukwulobe, Iyore Evelyn; Ademola , Ibukunolu Adebiyi; Alabi, Ibraheem A. (FKIP - Universitas Riau, 2025)
Cooperative learning such as team-pair-solo strategy, gives teachers a framework to help students grasp scientific knowledge and cross-cutting mathematics ideas for enhanced performance..This study explored the effect of team-pair-solo strategy on senior secondary school students’ performance in mathematics. It adopted quasi-experimental research design of pre-test, post-test non-equivalent control group of 2x2 factorial design.. Two public schools in Badagry zone of Education District V, Lagos State, Nigeria, with 139 students (60-experimental & 79-control groups) in two intact classes of Senior Secondary School two made up the study sample. Mean, standard deviation and Analysis of Covariance were employed using IBM-SPSS 23. Mathematics Achievement Test (MAT) with reliability index of 0.87 was employed. Results showed that students' performance in team-pair-solo is significantly better than those in conventional classroom [F(1,138)=10.688;p<0.05],no statistically significant gender differences in students’ performances in either group [F (1, 138) = 0.029; p>0.05] and no significant interaction effect of treatment and gender on student performance in mathematics [F (1, 138) = 0.095; p>0.05. The study concluded that the adoption of team-pair-solo strategy significantly enhanced performance of students in mathematics and it is recommended that Mathematics educators publicize of the use of this strategy to enhance students’ performance in Mathematics.